Interaction of TM6SF2 E167K and PNPLA3 I148M variants in NAFLD in northeast China - Min Xu; Yiling Li; Shuang Zhang; Xinyi Wang; Jianhua Shen; Shuwen Zhang (Annals of Hepatology, 2019)
Introduction and aim: This study aimed to confirm the association of the transmembrane 6 superfamily member 2 (TM6SF2) E167K variant with non-alcoholic fatty liver disease (NAFLD) and the degree of steatosis, as well as the additive effect of body mass index (BMI) or the patatin-like phospholipase domain-containing protein 3 (PNPLA3) I148M and TM6SF2 E167K variants in NAFLD. Materials and methods: A total of 158 NAFLD patients and 158 matched controls were recruited. Steatosis was classified as mild, moderate and severe by FibroScan. Associations between the TM6SF2 E167K variant and NAFLD as well as clinical parameters were evaluated. Results: Although the frequency of the T allele was low in the Chinese population (MAF = 7.4%), there was still a significant association between the E167K variant and NAFLD (odds ratio = 3.379, 95% confidence interval: 1.500–7.612, P = 0.003). In particular, the TM6SF2 genotype was also associated with the degree of steatosis (P = 0.023). The TM6SF2 variant was associated with increased alanine aminotransferase (ALT) but no other clinical parameters, such as aspartate aminotransferase (AST), alkaline phosphatase (ALP) and lipids. Notably, we also found that an additive effect of the TM6SF2 E167K and PNPLA3 I148M variants in NAFLD. Furthermore, we did not identify an association between the TM6SF2 E167K variant and NAFLD in the non-obese population. Conclusion: The TM6SF2 E167K variant was associated with NAFLD in northeast China, and there was an interaction between the PNPLA3 I148M and TMS6F2 E167K variants in NAFLD.